The Role Of Innovation In Waste Management - Dib ,Badr Eddine; Harnan, Nadjoua (جامعة الوادي University of Eloued, 2025)
The increasing amount of waste daily in our time constitutes an important environmental and economic challenge, requiring the construction of integrated strategies aimed at creating an integrated management of this waste, based on innovative techniques and special technologies to deal with it and manage it in effective and safe ways. This study was designed to provide a comprehensive theoretical analysis of the innovation element, and examine The concept of various types of waste, to highlight the problem of waste management and the role of innovation in it by clarifying the most important strategies followed, as well as the various innovative techniques and modern technologies used in this, with a focus on the reality of solid waste management (domestic and similar) in the state of Khenchela, for the technical backfilling center as a model Innovative, we relied on conducted interviews and field observations, to convey a realistic simulation of the center’s working method, based on real data provided by it over a specific period of time, to apply an innovative waste management model, which contributed to analyzing the effectiveness of innovation in reducing the amount of waste sent to landfills, even if Relatively, enhancing the environmental and economic sustainability of waste management operations.
Keywords: Innovation; Waste; Waste Management